Land der Verheißung - Ort der Zuflucht Jüdische Emigration und nationalsozialistische Vertreibung aus Österreich nach Palästina 1920 bis 1945 - Kumar, Victoria (Studien Verlag, 2016)
The publication "Land of promise - place of refuge" addresses the emigration and flight of Austrian Jewish women and men to Palestine by embedding it in the history of the overall Palestine migration since the beginning of the 1920s. It focuses on the cooperation of the Jewish Community, the "Zentralstelle für jüdische Auswanderung" and the Palestine Office in Vienna, an institution, which barely has been researched so far. Furthermore the book deals with the policies and interests of the British mandatory power and the activities of the Jewish Agency and its associated institutions in Jerusalem.